Broadband terahertz spectroscopy of enantiomeric polylactide. (1st June 2023) - Ohnishi, S.; Hiroshiba, N.; Ebata, A.; Ohnishi, B.; Tsuji, H.; Tanaka, S.; Ariyoshi, S.
Abstract: In this study, poly (L-lactide) (PLLA), poly (D-lactide) (PDLA), and their blend (stereocomplex; SC) were investigated by terahertz spectroscopy. Absorption spectra were obtained for PLLA isothermally crystallized in a temperature range of 80 °C–140 °C, and eight characteristic peaks were observed in the frequency range of 1–15 THz. No obvious spectral difference between PLLA and PDLA was observed, indicating that chirality did not affect their spectra. Conversely, the SC sample exhibited a complex peak shift behavior that was different from those of the homo-crystals. To elucidate the origins of the vibration modes, the spectral measurement of the lactide was conducted and compared with the results of PLLA. Four absorption peaks that appeared below 8 THz disappeared in the experimental of the lactide. This suggests that the vibration modes in the polylactide differ around 8 THz, and low and higher frequencies are attributed to the inter- and intramolecular vibration modes, respectively.